1989
DOI: 10.1128/aac.33.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of quinolone resistance in Escherichia coli: characterization of nfxB and cfxB, two mutant resistance loci decreasing norfloxacin accumulation

Abstract: Two genetic loci selected for norfloxacin (nfxB) and ciprofloxacin (cfxB) resistance were characterized. Both mutations have previously been shown to confer pleiotropic resistance to quinolones, chloramphenicol, and tetracycline and to decrease expression of porin outer-membrane protein OmpF. nfxB was shown to map at about 19 min and thus to be genetically distinct from ompF (21 min Chemother. 32:1187Chemother. 32: -1191Chemother. 32: , 1988), suggest a model for quinolone resistance by decreased permeation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
86
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 44 publications
3
86
0
1
Order By: Relevance
“…Previous work has shown that, independently of soxRS, the soxQl and cfxBl mutations cause transcriptional activation of some of the soxRS regulon genes and the induction of seven other proteins not influenced by soxRS or elevated by oxidative stress (14). Both soxQl and cfxBl, together with the previously identified marRi, map to the 34-min locus on the E. coli chromosome (6,13,14,19), which has been implicated in chromosome-mediated multiple antibiotic resistance (mar) (6,13,16). The soxQl-and the cfxBl-dependent phenotypes do not depend on the soxRS locus, and gene induction by soxRS in response to redox stress does not depend on mar (14).…”
mentioning
confidence: 99%
“…Previous work has shown that, independently of soxRS, the soxQl and cfxBl mutations cause transcriptional activation of some of the soxRS regulon genes and the induction of seven other proteins not influenced by soxRS or elevated by oxidative stress (14). Both soxQl and cfxBl, together with the previously identified marRi, map to the 34-min locus on the E. coli chromosome (6,13,14,19), which has been implicated in chromosome-mediated multiple antibiotic resistance (mar) (6,13,16). The soxQl-and the cfxBl-dependent phenotypes do not depend on the soxRS locus, and gene induction by soxRS in response to redox stress does not depend on mar (14).…”
mentioning
confidence: 99%
“…In this second type of resistance, accumulation of the antibiotic within the cell may be diminished by reduced uptake or by increased efflux from the cell (33). These low-level broad resistances are usually mediated by chromosomal mutations (15,19,23,39), but few are well characterized either as regulatory systems or for the cellular mechanisms involved.…”
mentioning
confidence: 99%
“…A number of reports regarding chromosomal mutations that confer low-level resistance to a variety of antibiotics (10,14,19,29) have appeared. In most cases, however, little is known about either the identity of the gene designated by the resistance mutation or the cellular mechanisms affected by these mutations.…”
mentioning
confidence: 99%